The Application of the Joint Criminal Enterprise Doctrine in International Criminal Law for the Prosecution of Sexual Offences - Hartle, Chelsea (Stellenbosch : Stellenbosch University, 2015)
Thesis (LLM)--Stellenbosch University, 2015